Model Komunitas Pertanian Perkotaan Menuju Ketahanan Pangan Melalui Modal Sosial di Kabupaten Gresik: Urban Farming Community Model for Towards Food Security Through Social Capital in Gresik District - Indah, Pawana Nur; Risa, Gung; Yektiningsih, Endang; Amir, Indra Tjahaja (Jurnal Ilmiah Manajemen Agribisnis, 2024)
This study aims to analyze social capital and dimension strength of social capital owned by urban farming community in Gresik Regency and to understand the influence of social capital dimension to urban farming community development in Gresik Regency. The research was conducted in Gresik Regency. The sample in this study is determined by purposive sampling of 87 respondents in Gending Village, Kebomas District, Gresik Regency with criteria of community members who are active in implementing healthy life pattern and urban farming that has been running for at least 2 years. Primary data were obtained by direct interview using questionnaire. The data were analyzed using descriptive method and Partial Least Square (PLS). Based on the results of the study, Trust has positive and significant effect on Empowerment with T test result of 0.786> 1.96. This shows that trust has indeed contributed greatly to community development in Gresik Regency. Social norms have a positive and significant impact on empowerment with the results of T test 0.511> 1.96. This shows the variable of social norms gives a real effect to the empowerment of urban farming community in Gresik Regency. Social network has a positive and significant effect on the empowerment with the result of T test of 0.810> 1.96. This shows that the social network variables significantly affect the Community Development in Gresik Regency.